Cytomegalovirus pUL50 is the multi-interacting determinant of the core nuclear egress complex (NEC) that recruits cellular accessory NEC components - Sonntag, Ellen; Hamilton, Stuart T.; Bahsi, Hanife; Wagner, Sabrina; Jonjic, Stipan; Rawlinson, William D.; Marschall, Manfred; Milbradt, Jens (Journal of General Virology, 2016)
Nuclear egress of herpesvirus capsids through the nuclear envelope is mediated by the multimeric nuclear egress complex (NEC). The human cytomegalovirus (HCMV) core NEC is defined by an interaction between the membrane-anchored pUL50 and its nuclear co-factor pUL53, tightly associated through heterodimeric corecruitment to the nuclear envelope. Cellular proteins, such as p32/gC1qR, emerin and protein kinase C (PKC), are recruited by direct interaction with pUL50 for the multimeric extension of the NEC. As a functionally important event, the recruitment of both viral and cellular protein kinases leads to site-specific lamin phosphorylation and nuclear lamina disassembly. In this study, interaction domains within pUL50 for its binding partners were defined by co-immunoprecipitation. The interaction domain for pUL53 is located within the pUL50 N-terminus (residues 10-169), interaction domains for p32/gC1qR (100-358) and PKC (100-280) overlap in the central part of pUL50, and the interaction domain for emerin is located in the C-terminus (265-397). Moreover, expression and formation of core NEC proteins at the nuclear rim were consistently detected in cells permissive for productive HCMV replication, including two trophoblast-cell lines. Importantly, regular nuclear-rim formation of the core NEC was blocked by inhibition of cyclin-dependent kinase (CDK) activity. In relation to the recently published crystal structure of the HCMV core NEC, our findings result in a refined view of NEC assembly. In particular, we suggest that CDKs may play an important regulatory role in NEC formation during HCMV replication.
EVALuna2:8320

Proteomic analysis of the multimeric nuclear egress complex of human cytomegalovirus - Milbradt, Jens; Kraut, Alexandra; Hutterer, Corina; Sonntag, Ellen; Schmeiser, Cathrin; Ferro, Myriam; Wagner, Sabrina; Lenac, Tihana; Claus, Claudia; Pinkert, Sandra; Hamilton, Stuart T.; Rawlinson, William D.; et al. (Molecular & Cellular Proteomics, 2014)
Herpesviral capsids are assembled in the host cell nucleus before being translocated into the cytoplasm for further maturation. The crossing of the nuclear envelope represents a major event that requires the formation of the nuclear egress complex (NEC). Previous studies demonstrated that human cytomegalovirus (HCMV) proteins pUL50 and pUL53, as well as their homologs in all members of Herpesviridae, interact with each other at the nuclear envelope and form the heterodimeric core of the NEC. In order to characterize further the viral and cellular protein content of the multimeric NEC, the native complex was isolated from HCMV-infected human primary fibroblasts at various time points and analyzed using quantitative proteomics. Previously postulated components of the HCMV-specific NEC, as well as novel potential NEC-associated proteins such as emerin, were identified. In this regard, interaction and colocalization between emerin and pUL50 were confirmed by coimmunoprecipitation and confocal microscopy analyses, respectively. A functional validation of viral and cellular NEC constituents was achieved through siRNA-mediated knockdown experiments. The important role of emerin in NEC functionality was demonstrated by a reduction of viral replication when emerin expression was down-regulated. Moreover, under such conditions, reduced production of viral proteins and deregulation of viral late cytoplasmic maturation were observed. Combined, these data prove the functional importance of emerin as an NEC component, associated with pUL50, pUL53, pUL97, p32/gC1qR, and further regulatory proteins. Summarized, our findings provide the first proteomics-based characterization and functional validation of the HCMV-specific multimeric NEC.
EVALuna2:8226

pUL69 of Human Cytomegalovirus Recruits the Cellular Protein Arginine Methyltransferase 6 via a Domain That Is Crucial for mRNA Export and Efficient Viral Replication - Thomas, Marco; Sonntag, Ellen; Müller, Regina; Schmidt, Stefanie; Zielke, Barbara; Fossen, Torgils; Stamminger, Thomas (Journal of Virology, 2015)
The regulatory protein pUL69 of human cytomegalovirus acts as a viral mRNA export factor, facilitating the cytoplasmic accumulation of unspliced RNA via interaction with the cellular mRNA export factor UAP56. Here we provide evidence for a posttranslational modification of pUL69 via arginine methylation within the functionally important N terminus. First, we demonstrated a specific immunoprecipitation of full-length pUL69 as well as pUL69aa1-146 by a mono/dimethylarginine-specific antibody. Second, we observed a specific electrophoretic mobility shift upon overexpression of the catalytically active protein arginine methyltransferase 6 (PRMT6). Third, a direct interaction of pUL69 and PRMT6 was confirmed by yeast two-hybrid and coimmunoprecipitation analyses. We mapped the PRMT6 interaction motif to the pUL69 N terminus and identified critical amino acids within the arginine-rich R1 box of pUL69 that were crucial for PRMT6 and/or UAP56 recruitment. In order to test the impact of putative methylation substrates on the functions of pUL69, we constructed various pUL69 derivatives harboring arginine-to-alanine substitutions and tested them for RNA export activity. Thus, we were able to discriminate between arginines within the R1 box of pUL69 that were crucial for UAP56/PRMT6-interaction and/or mRNA export activity. Remarkably, nuclear magnetic resonance (NMR) analyses revealed the same ?-helical structures for pUL69 sequences encoding either the wild type R1/R2 boxes or a UAP56/PRMT6 binding-deficient derivative, thereby excluding the possibility that R/A amino acid substitutions within R1 affected the secondary structure of pUL69. We therefore conclude that the pUL69 N terminus is methylated by PRMT6 and that this critically affects the functions of pUL69 for efficient mRNA export and replication of human cytomegalovirus.The UL69 protein of human cytomegalovirus is a multifunctional regulatory protein that acts as a viral RNA export factor with a critical role for efficient replication. Here, we demonstrate that pUL69 is posttranslationally modified via arginine methylation and that the protein methyltransferase PRMT6 mediates this modification. Furthermore, arginine residues with a crucial function for RNA export and for binding of the cellular RNA export factor UAP56 as well as PRMT6 were mapped within the arginine-rich R1 motif of pUL69. Importantly, we demonstrated that mutation of those arginines did not alter the secondary structure of R1, suggesting that they may serve as critical methylation substrates. In summary, our study reveals a novel posttranslational modification of pUL69 which has a significant impact on the function of this important viral regulatory protein. Since PRMTs appear to be amenable to selective inhibition by small molecules, this may constitute a novel target for antiviral therapy.
EVALuna2:8296

The Prolyl Isomerase Pin1 Promotes the Herpesvirus-Induced Phosphorylation-Dependent Disassembly of the Nuclear Lamina Required for Nucleocytoplasmic Egress - Milbradt, Jens; Hutterer, Corina; Bahsi, Hanife; Wagner, Sabrina; Sonntag, Ellen; Horn, Anselm; Kaufer, Benedikt B.; Mori, Yasuko; Sticht, Heinrich; Fossen, Torgils; Marschall, Manfred (PLoS Pathogens, 2016)
The nuclear lamina lines the inner nuclear membrane providing a structural framework for the nucleus. Cellular processes, such as nuclear envelope breakdown during mitosis or nuclear export of large ribonucleoprotein complexes, are functionally linked to the disassembly of the nuclear lamina. In general, lamina disassembly is mediated by phosphorylation, but the precise molecular mechanism is still not completely understood. Recently, we suggested a novel mechanism for lamina disassembly during the nuclear egress of herpesviral capsids which involves the cellular isomerase Pin1. In this study, we focused on mechanistic details of herpesviral nuclear replication to demonstrate the general importance of Pin1 for lamina disassembly. In particular, Ser22-specific lamin phosphorylation consistently generates a Pin1-binding motif in cells infected with human and animal alpha-, beta-, and gammaherpesviruses. Using nuclear magnetic resonance spectroscopy, we showed that binding of Pin1 to a synthetic lamin peptide induces its cis/trans isomerization in vitro. A detailed bioinformatic evaluation strongly suggests that this structural conversion induces large-scale secondary structural changes in the lamin N-terminus. Thus, we concluded that a Pin1-induced conformational change of lamins may represent the molecular trigger responsible for lamina disassembly. Consistent with this concept, pharmacological inhibition of Pin1 activity blocked lamina disassembly in herpesvirus-infected fibroblasts and consequently impaired virus replication. In addition, a phospho-mimetic Ser22Glu lamin mutant was still able to form a regular lamina structure and overexpression of a Ser22-phosphorylating kinase did not induce lamina disassembly in Pin1 knockout cells. Intriguingly, this was observed in absence of herpesvirus infection proposing a broader importance of Pin1 for lamina constitution. Thus, our results suggest a functional model of similar events leading to disassembly of the nuclear lamina in response to herpesviral or inherent cellular stimuli. In essence, Pin1 represents a regulatory effector of lamina disassembly that promotes the nuclear pore-independent egress of herpesviral capsids.
EVALuna2:8308